2019
DOI: 10.1128/aac.00757-19
|View full text |Cite
|
Sign up to set email alerts
|

The Likelihood of Developing a Carbapenem-Resistant Enterobacteriaceae Infection during a Hospital Stay

Abstract: Of 1,455 unique patients in U.S. intensive care units (ICUs), 4% were rectally colonized with CRE on admission. A total of 297 patients were initially negative for carbapenem-resistant Enterobacteriaceae (CRE) and remained in the ICU long enough to contribute additional swabs; 22% of these patients had a subsequent CRE-positive swab, with a median time to CRE colonization of 13 days (interquartile range, 7 to 21 days). Patients colonized with carbapenemase-producing CRE were more likely than those colonized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…However, theoretically, the therapeutic challenges associated with non-CP-CRE active infection resemble those of CPE [ 41 ], and therefore the exploration of the clinical and molecular epidemiological features of non-CP-CRE, and the mode of their acquisition and spread in hospitals, is still of paramount importance. Moreover, as displayed in our cohort as well [ 21 ], some asymptomatic carriers (4%), eventually develop active infection, including BSIs.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…However, theoretically, the therapeutic challenges associated with non-CP-CRE active infection resemble those of CPE [ 41 ], and therefore the exploration of the clinical and molecular epidemiological features of non-CP-CRE, and the mode of their acquisition and spread in hospitals, is still of paramount importance. Moreover, as displayed in our cohort as well [ 21 ], some asymptomatic carriers (4%), eventually develop active infection, including BSIs.…”
Section: Discussionsupporting
confidence: 68%
“…Even the 2015 guidelines by the Centers for Disease Control and Prevention do not differentiate between the 2 entities in terms of infection control-suggested measures (although it does acknowledge the issue) [ 10 ]. As depicted in this study and by others [ 15 , 16 , 20 , 21 ], the epidemiology of non-CP-CRE differ considerably from that of CPE, and therefore measures should be tailored based of controlled analyses.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Hospital stay represents a particularly high risk to be colonize or in developing an infection with a CRE. Recent studies found that CRE colonization among ICU patients showing new emerging mechanisms of resistance continue to rise in the United States of America [ 31 , 32 ]. There seems to have no different in other developed countries.…”
Section: Carbapenemases-producing Enterobacteriaceae mentioning
confidence: 99%